Kinetics of copper cementation on a rotating iron disc - Calara, Joven Villanueva
The kinetics of copper cementation on the rotating iron disc was found to be first order with respect to the cupric ion concentration. The rate increased non-linearly with the half-power of the spin rate. This departure from Levich's prediction was attributed to the overriding influence of the copper deposit on the kinetics. The activation energy above 45°C was found to be 4.89 Kcal/mole, in close agreement with values obtained in other investigations. This value supports the diffusion control model where the rate determining step is the transport of the cupric ion across a diffusion boundary layer. Below room temperature, the activation energy was found to be 11.79 Kcal/mole, indicating the presence of surface control, i.e., control other than pure diffusion. Sodium chloride in salt water concentration was found to improve the kinetics, attributed to the more freely peeling copper deposit that formed. A commercial flocculant was found to aid the formation of a dense, platy copper deposit that tended to block the cementation reaction. There was a decrease in the true rate in the presence of the flocculant.